Association between putative functional variants in the PSMB9 gene and risk of melanoma – re‐analysis of published melanoma genome‐wide association studies. (27th March 2013) - Qian, Ji; Liu, Hongliang; Wei, Sheng; Liu, Zhensheng; Li, Yangkai; Wang, Li‐E; Chen, Wei V.; Amos, Christopher I.; Lee, Jeffrey E.; ,; Iles, Mark M.; Law, Matthew H.; et al.
Summary To mine possibly hidden causal single‐nucleotide polymorphisms (SNPs) of melanoma, we investigated the association of SNPs in 76 M/G1 transition genes with melanoma risk using our published genome‐wide association study (GWAS) data set with 1804 melanoma cases and 1026 cancer‐free controls. We found multiple SNPs with P < 0.01 and performed validation studies for 18 putative functional SNPs in PSMB9 in two other GWAS data sets. Two SNPs (rs1351383 and rs2127675) were associated with melanoma risk in the GenoMEL data set (P = 0.013 and 0.004, respectively), but failed in validation using the Australian data set. Genotype–phenotype analysis revealed these two SNPs were significantly correlated with mRNA expression level of PSMB9. Further experiments revealed that SNP rs2071480, which is in high LD with rs1351383 and rs2127675, may have a weak effect on the promoter activity of PSMB9. Taken together, our data suggested that functional variants in PSMB9 may contribute to melanoma susceptibility.